Election Signs and Time Limits - Jules B. Gerard (Washington University Journal of Law & Policy, 2000)
This Essay deals with a question the United States Supreme Court has never answered directly, namely, whether a community may impose time limits on the periods during which signs carrying messages about election issues may be displayed. It begins with a brief survey of relevant Supreme Court decisions before coming to grips with that question.
Keywords: Land use; Political advertising; Signs and symbols